Enhancing Building Temperature Control Systems Using Advanced Fuzzy PID Algorithms - Sun, Yize (Transactions on Computer Science and Intelligent Systems Research, 2025)
The performance of traditional building temperature control systems is often suboptimal due to the inherent complexity of the control objects and the challenges associated with establishing accurate mathematical models. These traditional systems frequently result in energy inefficiency and compromised comfort levels for occupants. Addressing these shortcomings requires an innovative approach to temperature regulation. After a thorough review of existing indoor temperature regulation systems both domestically and internationally, it is evident that there is significant room for improvement. Combining insights from control theory with advanced algorithms, this study proposes the use of a fuzzy PID (Proportional-Integral-Derivative) algorithm to establish a more effective temperature control system. The fuzzy PID algorithm integrates the robustness of PID control with the adaptability of fuzzy logic, providing a more responsive and precise method for temperature regulation. This hybrid approach leverages fuzzy logic to handle the uncertainties and nonlinearities in the control process, adjusting the PID parameters in real-time to optimize performance. As a result, the new system can dynamically respond to changing environmental conditions and occupant needs, maintaining a comfortable indoor climate while minimizing energy consumption.